Optimization of blending-based products - Yunus, N. A. (Elsevier B.V., 2017)
The majority of chemical-based products are mixtures of two or more substances. It is because a single chemical does not always satisfy the product needs. Mixing or blending is a simple process in chemical engineering where two or more chemicals were added and mixed to achieve the desired needs. Designing blended products has some challenges. One of the challenges is to find a balance formulation (chemicals and the mixture fractions) so that all the desired needs and performance are fulfilled. Blending of chemicals with appropriate selection of the chemicals could offer advantages, such as enhancing product attributes, increasing the product safety by replacing harmful chemical with safer chemicals, reducing the consumption of nonsustainable materials, as well as reducing pollutants’ release to the atmosphere. Another challenge is the model reliability, where solving the blending problem using a mathematical approach requires property models that are predictive and accurate. Another challenge is the size of the blending problem, which can become a huge problem and increase exponentially with the size of the database and type of mixture. Solving a huge problem mathematically requires extensive computational efforts and may cause nonconvergence results.